Frequency-dependent orthotropic damping properties of Nomex honeycomb composites - Zhou, Yong; Liu, Anna; Xu, Yongzheng; Guo, Yunli; Yi, XiaoSu; Jia, Yuxi (Elsevier Ltd, 2020)
In this paper, the orthotropic damping behavior of Nomex honeycomb composites and its causes are investigated. The needed specimen sizes for the measurement of the frequency-dependent transverse shear moduli (TSM) and fundamental damping coefficients of the honeycomb cores were analyzed at first. Then, the effects of cell side length and beam orientation on the orthotropic damping properties were explored. The results reveal that relatively high TSM (GLT) and damping values (ηWT) can be obtained by decreasing the cell side length without adding any additional weight. Damping mechanism analysis indicates that the difference in damping contribution of the interfacial phase to honeycomb core in different directions leads to the orthotropic damping behavior of honeycomb core. This study is helpful to guide the TSM measurement and structure design of honeycomb composites.